Kutadgu Bilig’de söz yapımı - Taş, İbrahim (My University, 2005)
Kutadgu Bilig'de Söz Yapımı iki ana bölümden oluşmaktadır: 1. Giriş, 2. Söz Yapımı. Giriş bölümünde Kutadgu Bilig ile ilgili kısaca bilgi verilmiş, bu eser üzerinde söz yapımına ilişkin yapılan çalışmalar eleştirel bir gözle değerlendirilmiştir. İkinci ve asıl bölüm olan Söz Yapımı ise başlıca dört alt bölüme ayrılmaktadır: 1. Addan Ad Türeten Ekler, 2. Addan Eylem Türeten Ekler, 3. Eylemden Ad Türeten Ekler, 4. Eylemden Eylem Türeten Ekler. Bu dört bölümde Kutadgu Bilig'deki türemiş sözcüklerin türeme yolları gösterilmiş, ekler anlamsal işlevlerine göre değerlendirilmiştir. Bu arada dipnotlarda da eserde geçen sözcükler üzerinde yapılan okuma, anlama ve etimoloji tartışmaları değerlendirilmiştir. Böylece bu çalışmayla birlikte yeni bir Kutadgu Bilig metni hazırlamaya imkân hazırlanmıştır.

This study consists of two sections: 1. Introduction, 2. Word Formation. In the introduction, we provided a brief information about Kutadgu Bilig as well as a critique of the previos studies which examine the work from the viewpoint of word formation. Second section is composed of four major subsections: 1. The suffixes that produce nouns from nouns, 2. The suffixes that produce verbs from nouns, 3. The suffixes that produce nouns from verbs, 4. The suffixes that produce verbs from verbs. In addition, we demonstrated the ways of the derivation of the derivative words, and discussed the suffixes from the stand point of their functions. In the footnotes, we will examine the previous discussions revolving around the etimology of the words in the work as well as the reading and understanding of them. So this study allows us to prepare a new critical edition of the Kutadgu Bilig.
Keywords: Türk Dili